Genetic potential and stability of carotene content in cassava roots - Iglesias, C.A.; Mayer, Jorge Edgard; Chavez, L.; Calle, F. (Springer, 1997)
People in vast areas of the tropics suffer from vitamin A deficiency, resulting in progressive eye damage and eventually leading to blindness. Improving the content of vitamin A precursors in staple crops could alleviate or solve such a problem. The objective of this work was to study the range of variability for carotene content in a sub-set of the global cassava germplasm collection, and to determine the inheritance of carotenes, as well as their stability in response to different processing methodologies. Genotypes with more than 2 mg carotenes/100 g of fresh roots have been selected as parental material for population development. Although root colour is highly correlated with carotene content, a quantitative evaluation of genotypes selected by colour is required in order to increase the efficiency of selection. Relatively few major genes are involved in the determination of carotene accumulation in cassava roots. Stability of carotenes in response to different processing methods is genotypically dependant, representing a trait to be evaluated after selecting for high carotene concentration in fresh roots. The results from this work have provided the basis for defining future strategies for the improvement of the nutritional quality of cassava.